2019
DOI: 10.1029/2019jc015163
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of Salinity Anomalies Associated With the Positive Indian Ocean Dipole

Abstract: Mechanisms of salinity anomalies associated with the positive Indian Ocean Dipole (pIOD) are investigated through a series of sensitivity experiments and an online budget analysis using a regional ocean model. Special emphasis is placed on the contribution from the rectified effects due to high-frequency variability, which was not quantitatively discussed in previous studies. The results from sensitivity experiments show that positive sea surface salinity (SSS) anomalies in the southeastern tropical Indian Oce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 59 publications
(125 reference statements)
1
26
0
Order By: Relevance
“…2d) has now developed a positive loading over the SSSI region, and a more concentrated positive loading is observed over the SSSP region with a weakening south of 108S. This pattern of SSS anomaly during SON is plausibly associated with the development of the ENSO and IOD events (Ballabrera-Poy et al 2002;Grunseich et al 2011;Singh and Delcroix 2011;Kido et al 2019).…”
Section: Singular Value Decompositionmentioning
confidence: 90%
“…2d) has now developed a positive loading over the SSSI region, and a more concentrated positive loading is observed over the SSSP region with a weakening south of 108S. This pattern of SSS anomaly during SON is plausibly associated with the development of the ENSO and IOD events (Ballabrera-Poy et al 2002;Grunseich et al 2011;Singh and Delcroix 2011;Kido et al 2019).…”
Section: Singular Value Decompositionmentioning
confidence: 90%
“…The last three terms represent subsurface processes: vertical advection, vertical mixing, and entrainment, respectively. The mixed layer heat budget is closed in the ROMS experiment 75,78 .…”
Section: Roms Mixed Layer Heat Budget Analysismentioning
confidence: 99%
“…This model is integrated for the period 1958-2014 following a 30-year spin-up under climatological forcing, and we analyze for 1960-2014. See Shchepetkin and McWilliams (2005) and Kido et al (2019) for more details about the model and Kusunoki et al (2020) for its validation in the southeastern Indian Ocean, particularly for the Ningaloo Niño (see Text S1). suggested that the recent shift to the negative phase of the IPO promoted more frequent occurrence of the Ningaloo Niño.…”
Section: Data and Modelsmentioning
confidence: 99%